THE IMPLEMENTATION ANALYSIS OF E-GOVERNMENT USING E-BPJS KESEHATAN IN HARJAMUKTI CIREBON: A CASE STUDY - Aos, Aos; Lituhayu, Dyah; Kismartini, Kismartini (Tatar Pasundan: Jurnal Diklat Keagamaan, 2023)
The mechanism for paying BPJS contributions using a virtual account system is considered inflexible; although administratively collective payments are deemed more efficient, the potential for reducing the collectability of contributions is remarkably high. For this reason, this study aims to analyze the implementation of e-government using BPJS Kesehatan Mandiri virtual account system in Harjamukti Sub-district, Cirebon City. The research was conducted using qualitative methods. Data collection techniques were carried out through literature studies, observations, and interviews. The selection of informants in the study employed purposive sampling against 3 employees and 10 families. The results concluded that e-government using BPJS Health Mandiri virtual account system in Harjamukti Sub-district, Cirebon City, had taken into account Van Horn and Van Meter policy implementation variables: policy standards and objectives, resources, inter-organizational communication, characteristics of implementing agents, and the disposition of the implementer. In the present context, the social, economic, and political circumstances continue to be limited by the unpredictable nature of communal revenue.Â Keywords: E-Government; The BPJS Kesehatan; Virtual Account System; Contribution